A Conceptual-Methodological Framework to Investigate the Mathematical Practices with DGS in Secondary Students - Carlos Roberto Pérez Medina (Social Education Research, 2023)
This contribution presents a conceptual-methodological framework to study mathematical practices from the instrumental aspect inherent to the activity of learning instrumented with Dynamic Geometry Systems (DGS) of a student at a secondary school [In Argentina, secondary education is compulsory training for young people from 12 to 17 years old]. This framework has a conceptualization of the mathematical practice with Dynamic Geometry Systems and a method to favour its operationalization. The framework has been built from diverse theoretical perspectives, in the environment of ergonomic approach of instrumental approximation in a didactical perspective and a qualitative methodology. The method to define the practice indicators that allow to identify it in the field is illustrated with parts of the results of the research in which it originated. One important implication of the framework is that it values, from a didactical perspective, the instrumental character of the activity of using Dynamic Geometry Systems in students that learn geometry, through a concrete definition of mathematical practices with Dynamic Geometry Systems and the operationalization of its analysis for a geometry content. This framework is an original contribution that refers to the knowledge about the existence of mathematical practices with Dynamic Geometry Systems about the content of school geometry.